Bamboo fiber based cellulose nanocrystals/poly(Lactic Acid)/Poly(Butylene Succinate) nanocomposites: morphological, mechanical and thermal properties - Rasheed, Masrat; Jawaid, Mohammad; Parveez, Bisma (Multidisciplinary Digital Publishing Institute, 2021)
The purpose of this work was to investigate the effect of cellulose nanocrystals (CNC) from bamboo fiber on the properties of poly (lactic acid) (PLA)/poly (butylene succinate) (PBS) composites fabricated by melt mixing at 175 °C and then hot pressing at 180 °C. PBS and CNC (0.5, 0.75, 1, 1.5 wt.%) were added to improvise the properties of PLA. The morphological, physiochemical and crystallinity properties of nanocomposites were analysed by field emission scanning electron microscope (FESEM), Fourier-transform infrared spectroscopy (FTIR) and X-ray diffractometry (XRD), respectively. The thermal and tensile properties were analysed by thermogravimetic analysis (TGA), Differential scanning calorimetry (DSC) and Universal testing machine (UTM). PLA-PBS blend shows homogeneous morphology while the composite shows rod-like CNC particles, which are embedded in the polymer matrix. The uniform distribution of CNC particles in the nanocomposites improves their thermal stability, tensile strength and tensile modulus up to 1 wt.%; however, their elongation at break decreases. Thus, CNC addition in PLA-PBS matrix improves structural and thermal properties of the composite. The composite, thus developed, using CNC (a natural fiber) and PLA-PBS (biodegradable polymers) could be of immense importance as they could allow complete degradation in soil, making it a potential alternative material to existing packaging materials in the market that could be environment friendly